2017
DOI: 10.1111/jpn.12739
|View full text |Cite
|
Sign up to set email alerts
|

Xanthophylls increased HDLC level and nuclear factor PPARγ, RXRγ and RARα expression in hens and chicks

Abstract: SummaryThis study was designed to investigate effects of xanthophylls on serum lipid profile (triglyceride, TG; cholesterol, CHO; high-density lipoprotein cholesterol, HDLC; and low-density lipoprotein cholesterol, LDLC) and nuclear factor (peroxisome proliferatoractivated receptor gamma, PPARγ; PPAR gamma coactivator 1 alpha, PGC1α; retinoid X receptor gamma, RXRγ; and retinoic acid receptor alpha, RARα) gene expression of breeding hens and chicks. In experiment 1, 432 hens were divided into three groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Our previous study has shown that intraperitoneal injection of LPS can cause intestinal villi atrophy, intestinal microflora change, intestinal inflammation and oxidative damage ( Gao et al, 2018a ). Hence, we established an immunological stress model of broilers (1 mg/kg LPS challenge was performed intraperitoneally at 21, 23, and 25 d of age), demonstrated that LPS injection induced significant growth performance degradation and intestinal inflammatory responses in broilers ( Gao et al, 2018b ). Therefore, some safe and effective nutritional additives to modulate the immune function are of great significance to protect chicken from immunological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that intraperitoneal injection of LPS can cause intestinal villi atrophy, intestinal microflora change, intestinal inflammation and oxidative damage ( Gao et al, 2018a ). Hence, we established an immunological stress model of broilers (1 mg/kg LPS challenge was performed intraperitoneally at 21, 23, and 25 d of age), demonstrated that LPS injection induced significant growth performance degradation and intestinal inflammatory responses in broilers ( Gao et al, 2018b ). Therefore, some safe and effective nutritional additives to modulate the immune function are of great significance to protect chicken from immunological stress.…”
Section: Introductionmentioning
confidence: 99%
“…The current hypothesis that lutein Accepted manuscript could improve body composition was primarily based on the interaction of lutein with the nuclear receptors such as retinoic acid receptor (RAR), retinoid X receptor (RXR) and peroxisome proliferator-activated receptors (PPARs) and subsequent increase in energy expenditure (Figure 3). Data from animal or in vitro studies demonstrated that lutein and its metabolites, as natural agonists for the nuclear RAR could activate RAR/RXR heterodimers which interact with retinoic acid response elements located in the retinoic acid-responsive genes and thereby regulate transcription of various genes involved in adipocyte metabolisms such as CCAAT-enhancer binding protein (C/EBPs) and PPARs (46)(47)(48)(49) . Moreover, lutein may also involve in the expression of PPARs target genes.…”
Section: Discussionmentioning
confidence: 99%
“…3). Data from animal or in vitro studies demonstrated that lutein and its metabolites, as natural agonists for the nuclear retinoic acid receptor, could activate retinoic acid receptor/retinoid X receptor heterodimers which interact with retinoic acid response elements located in the retinoic acid-responsive genes and thereby regulate transcription of various genes involved in adipocyte metabolisms such as CCAAT-enhancer binding protein and PPAR (46)(47)(48)(49) . Moreover, lutein may also involve in the expression of PPAR target genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, few data are available which examine the effects of lutein supplementation on hematologic and hepatic parameters in hens. Adding lutein at 40 mg/kg in the diet of laying hens increased cyclooxygenase-2, inducible nitric oxide synthase, caspase-3, B cell lymphoma/leukemia-2 and HDL cholesterol in the liver, but did not increase serum triglycerides, cholesterol and LDL ( Gao et al., 2018 ). Adding marigold flower meal did not affect the content of crude fat and cholesterol in the yolk of Hy-Line gray hens ( Xin et al., 2022 ).…”
Section: Application Of Lutein In Laying Hensmentioning
confidence: 99%